Methods to disinfect and decontaminate SARS-CoV-2: a systematic review of in vitro studies. (March 2021) - Kwok, Chun Shing; Dashti, Mustafa; Tafuro, Jacopo; Nasiri, Mojtaba; Muntean, Elena-Andra; Wong, Nicholas; Kemp, Timothy; Hills, George; Mallen, Christian D.
Background: Cleaning is a major control component for outbreaks of infection. However, for the SARS-CoV-2 pandemic, there is limited specific guidance regarding the proper disinfection methods that should be used. Methods: We conducted a systematic review of the literature on cleaning, disinfection or decontamination methods in the prevention of SARS-CoV-2. Results: A total of 27 studies were included, reporting a variety of methods with which the effectiveness of interventions were assessed. Virus was inoculated onto different types of material including masks, nasopharyngeal swabs, serum, laboratory plates and simulated saliva, tears or nasal fluid and then interventions were applied in an attempt to eliminate the virus including chemical, ultraviolet (UV) light irradiation, and heat and humidity. At body temperature (37°C) there is evidence that the virus will not be detectable after 2 days but this can be reduced to non-detection at 30 min at 56°C, 15 min at 65°C and 2 min at 98°C. Different experimental methods testing UV light have shown that it can inactivate the virus. Light of 254–365 nm has been used, including simulated sunlight. Many chemical agents including bleach, hand sanitiser, hand wash, soap, ethanol, isopropanol, guandinium thiocynate/t-octylphenoxypolyethoxyethanol, formaldehyde, povidone-iodine, 0.05% chlorhexidine, 0.1% benzalkonium chloride, acidic electrolysed water, Clyraguard copper iodine complex and hydrogen peroxide vapour have been shown to disinfect SARS-CoV-2. Conclusions: Heating, UV light irradiation and chemicals can be used to inactivate SARS-CoV-2 but there is insufficient evidence to support one measure over others in clinical practice.